Investigation of daylight performance in traditional residential buildings in the context of EN- 17037 standard - Sivas Hubiyar Korucu Mansion - Özlem Sümengen; Gamze Merve Şengönül (Journal of Design for Resilience in Architecture and Planning, 2022)
Daylight is an integral part of our lives as the most important element in places. Efficient and appropriate use of daylight reduces the need for adequate illumination of the volumes and artificial lighting. Today, windows that are not designed correctly cause energy waste by increasing the use of artificial lighting instead of natural lighting. The seriousness of this situation is increasing today and regulations and standards regarding daylight use are published. The disappearance of this traditional Turkish architecture has also reduced the effective use of natural light. Study is focused on daylight penetration in traditional Turkish houses in the context of EN-17037 and a traditional Turkish house evaluated as case study. Natural lighting measurements of the selected building were calculated using the daylight simulation program, at 09:00, 12:00 and 15:00 for the months of March 21, June 21, September 21, and December 21 under average sky conditions. In line with the results obtained from the simulation program, the illumination levels (Lux), daylight factor (DF) and daylight performance classification (%) of the spaces are presented. As a result of the evaluation made in the context of EN 17037 standard, attention was drawn to the importance of openings as windows in traditional Turkish houses. And additionaly, architectural similarities and differences with the contemporary building is highlighted in results.